The genome sequence of the Olive Pearl, Udea olivalis (Denis & Schiffermüller, 1775) - Boyes, D; Holland, PWH (F1000 Research Ltd, 2023)
We present a genome assembly from an individual male Udea olivalis (the Olive Pearl; Arthropoda; Insecta; Lepidoptera; Crambidae). The genome sequence is 624.4 megabases in span. Most of the assembly is scaffolded into 31 chromosomal pseudomolecules, including the Z sex chromosome. The mitochondrial genome has also been assembled and is 15.3 kilobases in length.